Systematic review and meta-analysis in medical research - JIN Zhichao (Shanghai yufang yixue, 2023)
In order to facilitate systematic reviews and meta-analyses by medical researchers， this paper provides a tutorial-style review of the relevant concepts， necessary steps， and some key considerations in conducting systematic reviews and meta-analyses. Specifically， it offers detailed explanations on literature search， evaluation of study bias， effect size selection， outcomes pooling， and testing and correction of publication bias. Additionally， the paper provides references to softwares and literature for implementing the methods， and concludes with a brief overview of the requirements for writing research papers.